Perompakan Di Selat Internasional (Environmental Issue): Tanggungjawab Negara Dalam Mengatasi Masalah Keamanan Di Lingkungan Perairan Selat Malaka - Muhammad Aldiansyah; Wahyu Abi Dwi Putra; Yasser Al Baihaqi; Muhammad Raihan Darmawan; Ema Septaria; Arimbi Fajari Furqon (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study explores the dynamics in the international maritime law system related to the handling of security cases in the Malacca Strait. Guides the reader through a journey from a general view to a focus on the core issues and opportunities in the international maritime law system related to the handling of security cases in the Malacca Strait. The pyramid begins with a broad context of what the problems are in the Malacca Strait, highlighting the importance of an effective response from the maritime law system of each country around the strait. This understanding opens a window into the complexity of the challenges faced by the authorities. The pyramid then tapers to how the role of countries around the strait to maintain the security of the Malacca Strait. An in-depth analysis of existing laws highlights the imprecise definition, a major limitation in dealing with the increasingly complex problems of the Malacca Strait. This study serves as a guide to understanding, identifying, and responding to issues and opportunities in the international maritime law system related to the security of the Malacca Strait. By detailing the obstacles and providing concrete solutions, this study is expected to be the basis for more adaptive and effective legal reform in an era that continues to evolve.